Binding of protofibrillar Aβ trimers to lipid bilayer surface enhances Aβ structural stability and causes membrane thinning. Issue 40 (5th October 2017) - Dong, Xuewei; Sun, Yunxiang; Wei, Guanghong; Nussinov, Ruth; Ma, Buyong
Abstract : Aβ–membrane interactions enhance structural stability of protofibrillar Aβ oligomers by stabilizing β-sheets and D23–K28 salt-bridges, and cause membrane perturbation by decreasing membrane's local thickness. Abstract : Alzheimer's disease, a common neurodegenerative disease, is characterized by the aggregation of amyloid-β (Aβ) peptides. The interactions of Aβ with membranes cause changes in membrane morphology and ion permeation, which are responsible for its neurotoxicity and can accelerate fibril growth. However, the Aβ–lipid interactions and how these induce membrane perturbation and disruption at the atomic level and the consequences for the Aβ organization are not entirely understood. Here, we perform multiple atomistic molecular dynamics simulations on three protofibrillar Aβ9–40 trimers. Our simulations show that, regardless of the morphologies and the initial orientations of the three different protofibrillar Aβ9–40 trimers, the N-terminal β-sheet of all trimers preferentially binds to the membrane surface. The POPG lipid bilayers enhance the structural stability of protofibrillar Aβ trimers by stabilizing inter-peptide β-sheets and D23–K28 salt-bridges. The interaction causes local membrane thinning. We found that the trimer structure related to Alzheimer's disease brain tissue (; Web:2M4J ) is the most stable both in water solution and at membrane surface, and displays slightly stronger membrane perturbation capability. These results provide mechanistic insights into the membrane-enhanced structural stability of protofibrillar Aβ oligomers and the first step of Aβ-induced membrane disruption at the atomic level.